Synchronous locally advanced rectal and prostate cancer: Dual tracer imaging with 18F-FDG-PET/CT and 68Ga-PMSA PET/CT - Sharjeel Usmani; Khulood Al Riyami; Syeda Sara Tajammul; Anjali Jain; Najeeb Ahmed (Journal of the Pakistan Medical Association, 2026)
Synchronous rectal and prostate malignancies are uncommon. Early diagnosis, accurate staging, and characterization of tumours are essential for selecting patient-tailored therapy. The origin of metastatic disease in synchronous cases presents a challenge for conventional imaging modalities but advances in molecular imaging have addressed this limitation. We report the case of a 72-year-old male with synchronous prostate and rectal cancer. Adoption of a dual PET/CT approach is essential for accurate staging and patient management. The combined molecular imaging approach significantly influenced staging and enabled individualized multidisciplinary management tailored to the biological behaviour and extent of each primary tumour. Keywords: 68Ga-PSMA PET/CT; 18F-FDG-PET/CT; synchronous tumours; prostate cancer